Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1001/archdermatol.2007.50
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and Ocular Signs of Childhood Rosacea

Abstract: To describe the clinical features of cutaneous and ocular manifestations of childhood rosacea, to propose diagnostic criteria, and to emphasize the possible severity of ocular complications in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
126
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(156 citation statements)
references
References 14 publications
(36 reference statements)
1
126
0
11
Order By: Relevance
“…However, in children, the dermatologic findings are often absent, making the diagnosis even more challenging and the identification of ocular manifestations especially important (15,17,57) . A study revealed ocular symptoms to precede skin features in 55% of children (58) . Ophthalmologists should maintain high suspicion in children with ocular surface disease, with or without cutaneous features, to avoid misdiagnosis and complications (59) .…”
Section: Diagnosis Of Pediatric Rosaceamentioning
confidence: 99%
See 3 more Smart Citations
“…However, in children, the dermatologic findings are often absent, making the diagnosis even more challenging and the identification of ocular manifestations especially important (15,17,57) . A study revealed ocular symptoms to precede skin features in 55% of children (58) . Ophthalmologists should maintain high suspicion in children with ocular surface disease, with or without cutaneous features, to avoid misdiagnosis and complications (59) .…”
Section: Diagnosis Of Pediatric Rosaceamentioning
confidence: 99%
“…The most common ocular signs in pediatric rosacea include meibomian gland dysfunction, telangiectasia, recurrent chalazia, conjunctival hyperemia, superficial punctate epitheliopathy involving the inferior cornea, as well as corneal infiltrates, pannus and neovascularization (16,58) . Phlyctenular keratoconjunctivitis has also been associated with ocular rosacea in children (17) .…”
Section: Pediatric Rosaceamentioning
confidence: 99%
See 2 more Smart Citations
“…Alvarenga suggested the use of doxycycline, 100 mg twice daily for 2-3 weeks, then tapering to 100 mg/day and later to 50 and 25 mg per day [3]. Tetracyclines however, are contraindicated for patients under 8 years old [7,8]. Miguel et al suggested the use of erythromycin for patients under 8 years old, and used it on their case series of two patients.…”
Section: Discussionmentioning
confidence: 99%